Prediction of tidal currents in the Inner Sound of the Pentland Firth using RTide (Proceedings of the European Wave and Tidal Energy Conference, 2025)
The design and operation of tidal stream energy farms will require the accurate prediction of tidal currents from field data. In the present paper we compare the performance of a physics based flow model, the traditional harmonic analysis method, and a newly developed code RTide. RTide is based on the Response Method proposed by Munk and Cartwright in the 1960s and uses machine learning to overcome the key disadvantages of their original approach. We use field data from the Meygen site in the Inner Sound of the Pentland Firth. We find RTide predictions based solely on the field data outperform both the flow model predictions and the currents predicted by harmonic analysis. Interestingly, feeding the physics-based flow model into RTide as an additional input does not outperform the predictions based on the field data alone. However, RTide can still be used as a correction tool to physics-based flow models.